Identificação dos fatores de riscos biológicos, quimicos e de resíduos no ambiente hospitalar - Cremer, Edivaldo (2011)
The conditions of environment, health and work security become essentials for the life quality of mankind and the citizenship rights, representing a big challenge for governments and organizations. For the health promotion in work, the occupational risks anticipation for prevention of accidents became indispensable. The present study aimed to the collection of occupational risk factors that the workers of hospital environment are exposed. The institution, study field, was a philanthropic hospital of interior of Paraná. Data were obtained by checklist validated in the protection measures against biological risks of Regulatory Norm 32, what establishes the guidelines about security and health of health services workers. The protection measures against biological risks inadequate to Regulatory Norm 32 represented 40,4%. Observed 41,5% of basins were inadequate and 39,4% of hospitalization units didn‟t have basins. Between the not-prohibited by employer were observed smoking habits and use of decoration in 50% of units, still, the drink consumption in working stages observed in 75% of units, however the sub items most worrying was the human resources training with 62,5% of inadequacy and 66,7% of protection measures against needlestick not contemplated. The protection measures against chemicals risks not contemplated represented 29,8% being the reutilization process of recipient, associated with the absence of label in fractioned products the items in more disagree. The protection measures against risk of not contemplated wastes were 33,3%. With respect to sub items was found 16,7% of inadequacy in packaging , 36,5% in segregation, 60% in temporary storage and 6,3% in transportation and external storage. Singly, needlestick were the most worrying sub item with 86,11% of inadequacy, represented by recapping and manual disconnect practices in needles, discard security device absence, packaging in reused chemical products gallons exceeded in your fill limit, carried in handcart with another wastes, temporarily packed of inadequate manner and identification and signalization absence in all that stages, doing in a unequivocal biological, chemical and residual risk. Concludes the several units showed biological, chemical and residuals risks. This conclusion enable to recommend intervention proposals in health services for the minimize existent risks, or simply the transformation in practice what the current legislation establishes, including the organizational restructuring, to request radical changes of environment and of the involved workers, promoting work security, accidents and occupational diseases prevention among the health professional workers.